-6z+12=24

Simple and best practice solution for -6z+12=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6z+12=24 equation:


Simplifying
-6z + 12 = 24

Reorder the terms:
12 + -6z = 24

Solving
12 + -6z = 24

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -6z = 24 + -12

Combine like terms: 12 + -12 = 0
0 + -6z = 24 + -12
-6z = 24 + -12

Combine like terms: 24 + -12 = 12
-6z = 12

Divide each side by '-6'.
z = -2

Simplifying
z = -2

See similar equations:

| -14-5n=2(5n+7)+5n | | (2x+3y)dx+(y+2)dy=0 | | -4s+15=25 | | (4x+2)+(5x-7)+3x=180 | | (2x-1)(5x^2+6x-3)= | | y^3+y=50 | | tanx=1.274 | | 187x=374 | | (2w^2-3w+1)(4w^2-7w-2)= | | 12=x+9-5x | | X+(-11)=13 | | x^2+y^2=1 | | (7x^2-5x-3)(2x+4)= | | X-(-9)=24 | | +2n=+4 | | 1/64 | | ln(3x-15)=5 | | y=x2+2 | | (3v-4)(2v^2+6v+7)= | | 5x-9=6(x+3) | | 3x+750+12x=200 | | F(x)=e^8x | | (5u^2+u-6)(u^2+3u-2)= | | 2^5x=3/2^7 | | 0,6427=x/7.5 | | 12/9600 | | 0,6427=e/7.5 | | 50-3x=8-9x | | K+8-7k=-22 | | 8+3f=14 | | 3x+6=-43-4x | | (3ax/9^2)^4 |

Equations solver categories